Determination of elemental composition of Lake Baikal sponges by wavelength dispersive X‐ray fluorescence spectrometry. (17th April 2013) - Chuparina, E.V.; Paradina, L. Ph.; Trunova, V.A.
Abstract : Sponge endemic species inhabit the Lake Baikal from the ancient times. Because the sponges are the biological filters of the Baikal water and they contribute greatly to silicon circulation in the lake, it is crucial to analyze their composition. Only a few publications report the analytical data concerning the element composition of Lake Baikal sponges. However, the analytical data were mainly obtained by destructive methods. No data on the concentrations of some alkaline and volatile elements are available so far. This article describes the application of wavelength dispersive X‐ray fluorescence spectrometry to study the sponges of Lubomirskia baicalensis, Baikalospongia bacillifera, and Baikalospongia recta species collected at the littoral part of the Beryozovy Cape in the Southern Baikal. The concentrations of 19 elements Na, Mg, Al, Si, P, S, Cl, K, Ca, Ti, Mn, Fe, Ni, Cu, Zn, Br, Rb, Sr, and Ba have been determined. In this article, we discuss the problem of selecting calibration samples for wavelength dispersive X‐ray fluorescence spectrometry, because appropriate reference samples are not available. The synthetic specimens, prepared by mixing plant certified reference materials and silicon dioxide in certain proportions, were proposed for calibration. The compositions of sponges cleaned from mineral particles and symbiotic organisms, as well as unwashed sponges, have been compared. Copyright © 2013 John Wiley & Sons, Ltd.